LA PRACTICA DE VALORES Y SU INCIDENCIA EN LAS ACTITUDES Y APTITUDES DE APRENDIZAJE DE LOS ESTUDIANTES DEL COLEGIO NACIONAL MIXTO ''URDANETA'' DE LA PARROQUIA RICAURTE, CANTON URDANETA PROVINCIA DE LOS RIOS, QUE AFRONTAN CONFLICTOS EN LA VIDA: FAMILIAR, ESTUDIANTIL Y SOCIAL. - PEDRO CARPIO CHELE (2006)
THE PRACTICE OF VALUES AND ITS IMPACT ON THE LEARNING ATTITUDES AND SKILLS OF THE STUDENTS OF THE NATIONAL MIXED SCHOOL ''URDANETA'' OF THE RICAURTE PARISH, CANTON URDANETA PROVINCE OF LOS RIOS, WHO FACE CONFLICTS IN LIFE: FAMILY, STUDENT AND SOCIAL .